SUFISTIC EDUCATION, A URGENCY OF AGE MODERNITY - Aliyah, Himatul; Supriyadi, Supriyadi (Journal Intellectual Sufism Research (JISR), 2018)
The life of modern society is identical with deification of science and technology, ruling out an understanding of religion . Sufism invites its adherents to think and dhikr, to use their minds intellectually optimally for the sake of the people to keep their hearts together in remembering Allah in the recitation of dhikr . Sufistic Education or Sufism need to be returned, applied and developed in human life so as to create as true individuals.